Zoneamento ecológico-econômico do município de Santa Cruz da Conceição-SP: uma proposta conceitual de planejamento para a sustentabilidade local - Araujo, Ronaldo Tavares de (Universidade Federal de São Carlos, 2008)
Due to the fact that governmental decisions centralize local sustainability as a basis for reaching global sustainability, planning and establishing directives for municipal territories are growingly important. Therefore, the objective of the present study was to characterize, analyze and elaborate a conceptual proposal for ecological-economical zoning in the city of Santa Cruz da Conceição, state of São Paulo, Brazil, using Geographical Information Systems GIS in order to create a digital georeferenced database that would enable the understanding of the structure and functioning of natural systems for the sustainable use of natural municipal resources. Characterization and zoning were based on topographical charts and aerial photographs. Results led to the construction of maps of structural elements in the landscape, analysis of erosion risks, and definition of zones of environmental fragility. For each zone, the problems, limitations and potentials were determined. Besides, tendency and directions were projected in order to determine general and specific directives for the preservation of natural characteristics and prioritization of the potentialities in each area. The municipal territory was divided into four zones that showed distinct levels of environmental fragility: zone of major relative environmental fragility (ZMAF), zone of medium relative environmental fragility (ZMEF), zone of major relative environmental stability (ZMAE) and urban zone (ZURB). ZMAF and ZMEF were predominant in the landscape of the city with 37.54% and 41.62% of the area, respectively. Results obtained evidenced the need to determine legal public, technical and financial tools for the social control of existing environmental impacts, to substitute and diversify socialeconomical matrices and to adequate the use of natural resources to local environmental fragilities.
Keywords: Ecologia; Zoneamento ecológico - econômico; Avaliação de riscos ambientais; Sistemas de Informação Geográfica; Local sustainability; Environmental planning; Economical-ecological zoning; Environmental management; CIENCIAS BIOLOGICAS::ECOLOGIA